2021
DOI: 10.1371/journal.pone.0249118
|View full text |Cite
|
Sign up to set email alerts
|

The impact of preferential trade agreements on bilateral trade: A structural gravity model analysis

Abstract: Trade agreements are thought to raise trade integration, but existing preferential trade agreements (PTAs) are insufficient in measuring market access of products. This study develops a product-based coverage index of PTAs using the World Trade Organization (WTO) preferential trade agreements and calculates bilateral trade measures using the EORA multi-regional input-output (MRIO) tables covering 189 countries worldwide over the period 1990–2015; the structural gravity model is employed to test how PTAs affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 64 publications
1
9
0
1
Order By: Relevance
“…With the proliferation of free trade agreements, there has been a surge in trade in intermediate goods. Recently, studies [38,39] analyzed the impact of PTAs on trade integration and global value chains (GVC) and showed that greater product liberalization could promote the development of the production network. Furthermore, the positive impacts of deep trade agreements on GVC integration were driven by value-added trade in intermediate, rather than final, goods and services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the proliferation of free trade agreements, there has been a surge in trade in intermediate goods. Recently, studies [38,39] analyzed the impact of PTAs on trade integration and global value chains (GVC) and showed that greater product liberalization could promote the development of the production network. Furthermore, the positive impacts of deep trade agreements on GVC integration were driven by value-added trade in intermediate, rather than final, goods and services.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Within the literature, the terms Free Trade Agreements (FTA) and Preferential Trade Agreements (PTA) are often used interchangeably, this report focuses on literature that explicitly focuses on PTAs. For example it is highlighted that in 2006, the South Asian Association for Regional Cooperation members formed their PTA (reffered to as the SAFTA -South Asian Free Trade Area) and the Association of Southeast Asian Nations member countries established the ASEAN Free Trade Area (AFTA) in 1992 to boost trade among member countries (Yao et al, 2021). In turn the Chinese Government identified that is has a number of trade agreements designated as twenty two FTAs and only one PTA.…”
Section: Preferential Trading Agreementsmentioning
confidence: 99%
“…There are global studies on the impact of preferential trade agreements, as [ 4 ] who did an analysis of 189 countries to identify the global production network and product-base coverage index, calculated in terms of intermediate good, final goods, commodities and services trade, over the period 1990–2015.…”
Section: Literature Review and Contextmentioning
confidence: 99%